Illness Expectations and Asthma Symptoms: A 6‐Month Longitudinal Study - Eleonora Volpato; Valentina Poletti; Paolo Banfi; Andrea Bonanomi; Francesco Pagnini (Health Expectations, 2025)
ABSTRACT Background After receiving a diagnosis, individuals often develop expectations about how their condition will evolve. This cognitive framework, known as ‘Illness Expectations’ (IEs), encompasses future‐oriented beliefs regarding the course of the illness and its symptoms. In chronic conditions such as asthma, IEs may play a critical role in shaping patient‐reported outcomes and clinical markers of disease progression. This study aims to empirically evaluate the impact of IEs on asthma symptoms and respiratory function. Methods A cohort of 310 individuals diagnosed with asthma was followed over a 6‐month period, with three assessment points. Asthma control was measured using the Asthma Control Test (ACT), while respiratory function was evaluated through forced expiratory volume in 1 s (FEV1) using spirometry. IEs were assessed using the validated ‘Illness Expectation Test’ (IET), which captures both explicit (conscious) and implicit (unconscious) expectations. Predictive analyses were conducted using latent growth modelling and linear regression to examine the influence of IEs on asthma symptoms and respiratory function over time. Results People with more negative explicit IEs about their asthma reported worse symptoms over time (β = −0.50, SE = 0.21, p = 0.01). Implicit IEs were not statistically significant (β = −0.014, SE = 0.008, p = 0.09). Explicit IEs about symptom progression were also associated with changes in lung function, with more negative expectations predicting greater declines in respiratory performance (β = 0.51, SE = 0.11, p = 0.001). Conclusions These findings suggest that IEs may be meaningfully associated with asthma outcomes, highlighting their potential relevance in understanding patient experiences and symptom perception. These results support further research into interventions targeting cognitive frameworks, with the aim of informing more personalised, patient‐centred approaches to asthma management. Patient or Public Contribution This study was developed in response to patient‐reported challenges in asthma management, particularly around understanding and managing IEs. Patients contributed to identifying key areas of concern, and their perspectives informed the choice of outcomes and tools. While direct involvement in recruitment and dissemination was limited due to the pandemic, the study's design and focus were guided by patient priorities, with potential applications in clinical consultations and future co‐designed interventions.